Assessment of Left Ventricular Functional Impairment in Patients With Chronic Kidney Disease Using Three‐Dimensional Speckle Tracking Imaging. - Gao, Xue; Xiao, Weiwei; Ji, Liqin; Li, Houyu; Zou, Anlingzi; Zhang, Xinru; Miao, Zhuomeng; Yang, Siyuan; Yu, Shaomei (Echocardiography, 2024)
Background: Chronic kidney disease (CKD) is strongly linked to the incidence and mortality of cardiovascular diseases (CVDs), with left ventricular myocardial damage being the most prevalent. This study aimed to assess left ventricle (LV) dysfunction using three‐dimensional speckle tracking imaging (3D‐STI) in CKD patients. Methods: A total of 110 CKD patients and 55 healthy volunteers underwent echocardiography. CKD patients were divided into CKD1 group and CKD2 group based on the estimated glomerular filtration rate (eGFR). Assessing cardiac function via two‐dimensional speckle tracking echocardiography (2D‐STE) and three‐dimensional speckle tracking echocardiography (3D‐STE) parameters, with strain presented in absolute terms. Collecting and comparing clinical and echocardiographic parameters from three groups, assessing 3D‐STI's value in evaluating LV functional impairment in CKD patients via correlation and receiver operating characteristic (ROC) curve analyses, and identifying risk factors for CKD progression to end‐stage renal disease (ESRD) through univariate and multivariate analyses. Results: In CKD2 group, 2D‐left ventricular ejection fraction (LVEF), 3D‐LVEF, 2D left ventricular global longitudinal strain (2D‐LVGLS), 3D‐LVGLS, and 3D‐left ventricular global circumferential peak strain (LVGCS) significantly worsen compared to the control and CKD1 groups, with statistically significant distinctions between the latter two (all p < 0.05). The absolute value of 3D‐LVGLS shows a robust correlation with N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) and serum creatinine (Scr) (r = −0.598, −0.649, both p < 0.001). ROC curve analysis indicates higher diagnostic efficacy of 3D‐LVGLS and 3D‐LVGCS for LV systolic function than 2D‐LVGLS. Univariate and multivariate analyses reveal an independent association of 3D‐LVGLS with the progression to ESRD in CKD. Conclusion: 3D‐LVGLS and 3D‐LVGCS effectively detect LV dysfunction in CKD patients. Specifically, 3D‐LVGLS demonstrates a robust correlation with NT‐proBNP and Scr and is independently linked to CKD progressing to ESRD.